Relationship of Mothers' Characteristic, Attitude, and Self Efficacy Toward Exclusive Breastfeeding Practice in Work Area of Tigaraksa Public Health Centre - Wulandari, Wulandari; Achmad fauzi (STIKep PPNI Jawa Barat, 2022)
Aims: Based on data from the Banten Province Health Office (Dinkes), the percentage of exclusive breastfeeding coverage in 2016 was around 55.75% (Profile of Banten Provincial Health Office, 2017). Exclusive breastfeeding coverage in 2014 was 27%, in 2015 it was 40%, in 2016 it was 50%, in 2017 it was 58.72% and in 2018 it was 41.59% (Tangerang District Health Profile, 2018). Objective: Examine the relationship between age, level of education and occupation, attitudes, and self-efficacy towards the practice of exclusive breastfeeding in the work area of ​​Tigaraksa Public Health Center, Tangerang Banten. Methods: This study employs quantitative techniques for associative analysis. Women who were breastfeeding their children between the ages of 6 months and 12 months comprised the study's population. One hundred people were randomly selected to participate in the study's samples. A questionnaire was employed to collect information for the study. Chi-square test was used for statistical analysis. Result: The results of this study show that: (1) breastfeeding mothers' age is related to their rates of exclusive breastfeeding (p = 0.000); (2) mothers' education is related to their rates of exclusive breastfeeding (p = 0.043); (3) mothers' employment status is related to their rates of exclusive breastfeeding (p = 0.000); (4) breastfeeding mothers' income is related to their rates of exclusive breastfeeding (p = 0.000) Conclusions and Suggestions: Mothers' exclusive breastfeeding rates at the Tigaraksa Public Health Center, Tangerang Banten, are related to their ages, levels of education, occupations, breastfeeding attitudes, and breastfeeding self-efficacy. Doctors, nurses, and lactation counselors, among others, should routinely provide support